Mental revolution in construction of ‘ilm tafsir and Sunnah: Malaysian experience - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (2017)
The construction involved the process of re-evaluation of the classical method in Quran and Sunnah studies; the importance and the application of the discipline of ‘ulum al-Quran in the interpretation of the Quran, and ‘ulum al-hadith in the commentary of aḥādīth so that the interpretation of religious texts (nuṣūṣ) may provide necessary relevant and practical solutions to problem facing the Muslim society. The construction of ‘ilm tafsir and Sunnah in Malaysia is quite advanced. However both are not formally established as a discipline of science.